2010
DOI: 10.4322/apa.2014.048
|View full text |Cite
|
Sign up to set email alerts
|

Associated fauna of Prasiola crispa (Chlorophyta) related to penguin rookery at arctowski (King George Island, South Shetland Islands, Maritime Antarctic)

Abstract: The samples of Prasiola crispa for study of associated fauna were collected on the rocks in the region adjacent to the penguin rookery at the Henri Arctowski Polish Research Station at (Admiralty Bay, Antarctic). The preliminary results showed that Tardigrades and Nematodes are the most abundant organisms of the associated fauna of P. crispa, being found in extremely high density. Others invertebrates were found in low densities (<70 ind.cm-2) along with Acari, Rotifer and Collembola. The specific identificati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…More recent studies showed that P. crispa is inhabited by rotifers (Suren 1990;Everitt 1981) and tardigrades (Dougherty & Harris 1963;Miller et al 1988;Miller & Heatwole 1996;Sohlenius et al 2004;Heatwole & Miller 2019). Other small animals are found in P. crispa (Sinclair et al 2006;Dalto et al 2010;De Mendonça et al 2012;Gantz et al 2018), including Belgica antarctica, the Antarctic endemic insect (Sugg et al 1983). It is likely that terrestrial algae provide favourable microhabitats for invertebrates, and some results indicate that arthropods prefer algae to mosses because of the feeding conditions (Bokhorst et al 2007).…”
Section: Discussionmentioning
confidence: 99%
“…More recent studies showed that P. crispa is inhabited by rotifers (Suren 1990;Everitt 1981) and tardigrades (Dougherty & Harris 1963;Miller et al 1988;Miller & Heatwole 1996;Sohlenius et al 2004;Heatwole & Miller 2019). Other small animals are found in P. crispa (Sinclair et al 2006;Dalto et al 2010;De Mendonça et al 2012;Gantz et al 2018), including Belgica antarctica, the Antarctic endemic insect (Sugg et al 1983). It is likely that terrestrial algae provide favourable microhabitats for invertebrates, and some results indicate that arthropods prefer algae to mosses because of the feeding conditions (Bokhorst et al 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Mouratov et al (2001) studied the negative correlation between the abundance of nematodes and soil moisture. Dalto et al (2010) studied the fauna associated with Prasiola crispa (Chlorophyta), a terrestrial green alga, nding the Plectus nematode in great abundance. Ileva-Makulec et al (2009) studied the abundance and trophic diversity of nematodes which increased with the age of ice-free areas.…”
Section: Introductionmentioning
confidence: 99%